2014
DOI: 10.1532/hsf98.2013272
|View full text |Cite
|
Sign up to set email alerts
|

Does Mild Renal Failure Affect Coronary Flow Reserve after Coronary Artery Bypass Graft Surgery?

Abstract: In our study, we detected a decrease in CFR in patients with mild renal failure. We believe that in patients undergoing CABG for coronary artery disease, mild renal failure can produce adverse effects due to deterioration of the microvascular bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
7
2
Order By: Relevance
“…In our study, all patients' age is greater than 65 years old. However, the age, as a HR for long-term mortality, shows no difference with other studies [ 7 , 9 - 12 ] .…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…In our study, all patients' age is greater than 65 years old. However, the age, as a HR for long-term mortality, shows no difference with other studies [ 7 , 9 - 12 ] .…”
Section: Discussioncontrasting
confidence: 68%
“…Garg et al [ 12 ] report had proved that off-pump or on-pump CABG surgery had no significant difference in the loss of kidney function within 1 year. Why mild preoperative RI decreased long-term mortality after CABG surgery is still being investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why mild preoperative renal insufficiency decreasing long-term mortality after isolated OPCAB surgery deserved to be further studied. Recently, Günday and colleagues [ 20 ] conducted a study included 52 consecutive patients with mild preoperative renal dysfunction vs. normal preoperative renal function undergoing uncomplicated CABG surgery, with respect to coronary flow reserve measured by a second harmonic trans-thoracic Doppler echocardiography. They found that although there was a significant increase in the mean coronary flow reserve after CABG surgery compared with baseline coronary flow reserve, patients with mild preoperative renal insufficiency compared with normal preoperative renal function have a significantly lower mean coronary flow reserve after CABG surgery (2.09 ± 0.08 vs. 2.37 ± 0.06, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Also well established have been significant correlations between mildly impaired renal function and coronary heart disease prognosis, [10] severity of coronary lesions, [11] and reduced coronary flow reserve in patients who have undergone coronary artery bypass grafting surgery. [12] Several equations employing creatinine levels have been used to estimate glomerular filtration rate (GFR). The Cockroft-Gault and Modification of Diet in Renal Disease (MDRD) equations have been widely used for this purpose.…”
mentioning
confidence: 99%